Trdnjava Evrope . Fortress Europe - Žilnik, Želimir; Trsar, Toni (Slovenia, 2001)
Soros Documentary Fund A film investigating economic migration within Europe. According to EU statistics, there are eight million refugees in Europe. In various degrees they all experience rootlessness, insecurity, exploitation but also the hard work and occasional bits of happiness. “Fortress Europe” cuts into what it really means to seek a better life in a continent entrenched to defend its own welfare and privileges. In this docudrama, asylum seekers talk about their plight and the impossible conditions European migration laws set for desperate people seeking a better life.